An efficient transformation of furano-hydroxychalcones to furanoflavones via base mediated intramolecular tandem O-arylation and C–O bond cleavage: a new approach for the synthesis of furanoflavones. Issue 42 (1st October 2015) - Sharma, Rajni; Vishwakarma, Ram A.; Bharate, Sandip B.
Abstract : An efficient transformation of furano-hydroxychalcones to furanoflavones via an intramolecular tandem O -arylation followed by C–O bond cleavage is described. Abstract : A new and efficient potassium carbonate mediated intramolecular tandem O -arylation followed by C–O bond cleavage of furano-hydroxychalcones is described. The treatment of furano-hydroxychalcones pongamol (1a ) and ovalitenone (2a ) with potassium carbonate in DMF led to the direct formation of the furanoflavones lanceolatin B (3ab ) and pongaglabrone (4ab ) in excellent yields. This is the first report on the cyclization of furano-hydroxychalcones via C–O bond cleavage (demethoxylation) to produce furanoflavonoids.